“The Caves of Steel”: Literary Devices to Reflect Social Issues in the Futuristic Cities - Akhmedov Rafael Sharifovich (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2026)
Isaac Asimov’s “The Caves of Steel” (1954) is often discussed as a foundational robot novel and a key text in the mid-century convergence of science fiction and detective fiction. This review article argues that the novel’s lasting critical value lies in the way its literary devices, especially spatial metaphor, genre hybridity, focalization, and the semiotics of the human/robot boundary, transform social anxieties into narrative structure. Drawing on scholarship in science fiction studies, urban cultural theory, and recent dissertation research, the article examines how Asimov’s enclosed-city chronotope represents overpopulation, class stratification, technological governance, and xenophobic othering in the futuristic city. Methodologically, the study combines a targeted literature review, device-centered close reading, and thematic coding of social-issue representations related to space, labor, prejudice, and technocracy. The findings indicate that Asimov’s strategy is not limited to simple allegorical substitution; rather, the detective plot performs a social-epistemological function by compelling both protagonist and reader to revise inherited assumptions about personhood, trust, and civic belonging. It further shows that the city itself operates as a formal mechanism that makes social contradictions visible, readable, and narratively manageable. The article concludes that “The Caves of Steel” remains an influential model of social science fiction in which narrative form itself stages debates about modernity’s infrastructural, ethical, and political limits.